THE ROLE OF OPTICAL FIBERS IN SOCIETY (Modern education and development, 2025)
The article discusses the basics and practical applications of disease detection based on neural networks. Neural networks, one of the most advanced branches of artificial intelligence, provide great opportunities for early detection of diseases in the medical field and effective organization of diagnostic processes. The article provides detailed information about the main types of neural networks, in particular, feedforward networks, convolutional networks (CNN), recurrent networks (RNN) and deep neural networks (DNN).